Multidisciplinary Treatment on a 69 years-old Male with Kidney Stone and Chronic Kidney Disease - Prabawati, Patricia; Kusuma, Raditya (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Introduction Obstruction by kidney stones is one of the causes of chronic kidney disease (CKD). Out of all CKD cases, 10.3% are associated with obstruction due to kidney stones. Treatment of kidney stones can restore kidney function, but requires holistic and intense collaboration between urologists to treat the stones, nephrologist to monitor kidney function, and nutritionists to provide proper diet to prevent kidney stone reccurence Case Presentation A 69-year old male presented to the emergency departement with flank pain since 1 week ago. The patient complained of frequent flank pain since the last year. BOF radiological examination found staghorn stones in the right kidney, and ultrasonography revealed severe hydronephrosis of the right kidney. An impaired kidney function and decreased eGFR related to CKD were also found. The urologist performed bivalve nephrolithotomy on the right kidney. Afterwards, a histopathological examination was done to determine the stone material for further collaborative management with internist and nutritionist. After consultation with nutritionists regarding nutritional needs, monitoring from internist was done to monitor comorbidities and progression of CKD. Kidney function was evaluated after collaborative management and we found improvement on kidney function. Discussion In patients with CKD caused by obstruction due to kidney stones, it is necessary to treat the kidney stones first to relieve obstruction and restore kidney function. In this case the role of the internist is to control and recover kidney function after urologists have relieved the patient from urinary obstruction. Kidney stones that have been successfully removed are subjected to histopathological examination to determine its composition. After the composition were identified, consultation with a nutritionist is carried out to determine the right diet for the patient. With the right diet, prevention of stone reoccurrence is expected. Conclusion A history of kidney stones is associated with an increased risk of CKD. Multidisciplinary collaboration between urologists, nephrologist, and nutritionists helps lower the risk of stone recurrence and minimize the need for additional operative procedures through a focus on dietary and medical approaches and improved kidney function.